Circular RNA 101368/miR-200a axis modulates the migration of hepatocellular carcinoma through HMGB1/RAGE signaling. Issue 19 (18th October 2018) - Li, Shaling; Gu, Huimin; Huang, Yan; Peng, Qian; Zhou, Rongrong; Yi, Panpan; Chen, Ruochan; Huang, Zebing; Hu, Xingwang; Huang, Yun; Tang, Daolin
ABSTRACT: Hepatocellular carcinoma (HCC), one of the most common type of cancers, is highly refractory to most systemic therapies. Understanding the genomic dysregulations, in particularly non-coding RNA (ncRNA) dysregulations, in HCC may provide novel strategies to HCC treatment. In our previous study, we demonstrated the key role of miR-200a-mediated HMGB1/RAGE signaling in HCC carcinogenesis. In the present study, we identified circular RNA (circRNA)-miRNA pair that might modulate the migration of HCC cell lines based on previously reported GEO database (GSE78520 and GSE43445) and investigated the function and molecular mechanism. circRNA-101368 was predicted by lncTar to target miR-200a, and the expression of circRNA-101368 was significantly upregulated in HCC tissue samples; the overexpression of circRNA-101368 was correlated with poorer prognosis in patients with HCC. Moreover, circRNA-101368 knockdown suppressed the migration and the protein levels of HMGB1, RAGE and NF-κB, while increased the E-Cadherin expression in HCC cell lines. As confirmed by luciferase reporter and RNA immunoprecipitation assays, circRNA-101368 directly bound to miR-200a to negatively regulate each other. The effect of circRNA-101368 knockdown on cell migration and HMGB1/RAGE signaling could be partially attenuated by miR-200a inhibition. In tissue samples, miR-200a was negatively correlated with circRNA-101368 and HMGB1, respectively, whereas circRNA-101368 and HMGB1 was positively correlated. Taken together, we demonstrated a network of circRNAs-miRNA-mRNA in HCC and provided a novel mechanism of HCC cell migration regulation.